EFISIENSI PENYERAPAN LOGAM Pb2+ DENGAN MENGGUNAKAN CAMPURAN BENTONIT DAN ENCENG GONDOK - M Faisal (Universitas Sumatera Utara, 2015)
Adsorption of Pb2+by using a mix of bentonite and water hyacinth has been carried out in a bacth system. The purpose of the research is to investigate the abilty of the mix bentonite and water hyacinth to adsorp Pb2+. Prior to adsorption process, the mix of bentonite and water hyacnth was activated physcally by H2SO4. The adsorption ability between activated-adsorbend and without activated-adsorbend was then compared. In the activaved process, the mix of bentonite and water hyacinth used was 4 gram in weight and 120 ml of H2SO4 1,2 M. In this research, adsorption time of 30, 60, 120 menit, the speed of 50, 100, 150 rpm and the Pb2+concentration of 30, 35 and 40 mg/l were used. The result showed that the adsorption efficiency of activated-adsorbend is higher than that of without activaved. The maximum adsorption of 0,987 mg/g were obtained at Pb2+concentration of 40 mg/l with a contact time and speed of 120 min and 150 rpm, respetively.